Insect-based protein feed for guinea fowl: Growth and egg laying performance under different feed regimes - Kere, B. A.; Pousga, S.; Somé, S.; Nianogo, A. J.; Anderson, A. K.; Kisaalita, William S. (African Journal of Food, Agriculture, Nutrition and Development, 2023)
Expansion of guinea fowl flock has been a challenge and one of the reasons is the low feed availability, especially in the dry season. The objective of this study was to contribute to the improvement of the nutritional situation of local guinea fowl with house fly larvae as a protein source. A total of 144 guinea fowls (Numida meleagris) of approximately 16 weeks old were grouped in batches of 12 and randomly distributed to four feeding treatments with three replications per treatment. Pre-egg laying and egg laying feed rations were formulated with different levels of sun-dried fly larvae and standard pre-egg laying and egg laying ration containing fishmeal as controls. The pre-egg-laying rations were served for 11 days, while the egg-laying rations were served for 58 days. The chemical composition of the formulated rations, individual Daily Feed Intake (DFI), Average Daily Gain (ADG), Feed Conversion Ratio (FCR), and number of eggs and eggs characteristics (weight, large diameter and shape index) were recorded for each treatment. The dried larvae-based feed showed the highest crude protein content compared to the control feed that was fishmeal-based. In addition, the results showed a relationship between the incorporated quantities of dried fly larvae and the resulting guinea fowl performances. For example, the highest DFI (63.35 g/bird; p≤0.05) and FCR (11.94; p≤0.05) were obtained in the group fed the pre-egg laying and egg-laying rations containing 25 % and 13 % fly larvae, respectively. However, the group fed the ration containing 16.67 % and 12.94 % of fly larvae in the pre-egg laying and egg laying phases, respectively, showed a DFI of 57.05 g/bird and an FCR of 9.09. These were similar to the values obtained for the control group (57.19 g/bird/day and 11.94, respectively), with a better ADG (2.91 g against 1.71 g). Egg laying performance (number of eggs) and egg characteristics (large diameter) were significantly improved (p <0.05) in favor of treatments including dried fly larvae with values proportional to incorporation quantities. Findings from the current study suggest that the incorporation of fly larvae in pre-egg-laying and egg-laying feeds significantly increased the performance of guinea fowls.